Peningkatan Literasi Keuangan dan Penyusunan Laporan Keuangan Mesjid Al-Amin Desa Sei Mencirim, Kecamatan Sunggal Kab. Deli Serdang, Sumatera Utara - Afriani, Selfi; Hubbul Wathan; Marlya Fatira; Rizki Syahputa (Politeknik Piksi Ganesha Indonesia, 2025)
Increasing Financial Literacy and Preparing Financial Reports for the Al-Amin Mosque aims to provide sharia financial literacy and help the mosque's financial reports to be prepared in accordance with accounting standards, especially ISAK 35 and well published. Currently the mosque is in the expansion renovation stage which has been going on for three years, but the progress of building the mosque is only 20%. Mosque financial reports and development financial reports are recorded conventionally and simply, which can only be seen on the al-Amin mosque notice board. Likewise, the management's understanding of financial literacy is indicated by the mosque's funds still being kept in conventional banks and the mosque's financial management is limited to mosque operational activities and the mosque management is also less active in Islamic finance-themed recitations so that if you look at the current progress of mosque construction it is directly proportional to the condition. Financial reports for both mosques and construction are not well published. The aim of the service activity is to educate and provide training to Al-Amin Mosque BKM administrators as well as Mosque BKM around Sei Mencirim Village about the obligation to prepare mosque financial reports in accordance with ISAK 35. In order to run the activities smoothly, the service team carried out data collection techniques by interviewing the Mosque BKM and direct survey by visiting the mosque location. The implementation method is by providing assistance in making financial reports to Accounting standards and sharia financial literacy training. The solution provided is by transferring knowledge and training in making financial reports according to ISAK 35 Accounting Standards, providing facilities in the form of Android televisions equipped with digital-based applications and providing teaching to the mosque BKM to make mosque financial reports using Excel referring to ISAK 35. Television can also display prayer schedules, Friday preacher schedules and other information regarding the condition of the mosque.